Violations of Service Fairness and Legal Ramifications: The Case of the Managed Care Industry - Chan, Marjorie (Journal of business ethics, 2002)
Adapted from Chan's (2000) model depicting success of litigation, this paper argues that with the application of various legislation, health maintenance organizations' (HMOs') violations of service fairness to each group: enrollees, physicians, and hospitals give rise to each group's lawsuits against the HMOs. Various authors (Bowen et al., 1999; Seiders and Berry, 1998) indicate that justice concepts such as distributive, procedural, and interactional justice can be applied to the area of service fairness. The violation of these underlying justice principles with HMOs' service unfairness to enrollees, physicians, and hospitals is examined. A general synopsis of the ethical issues in the managed care industry is provided. The various lawsuits launched by each group: enrollees, physicians, and hospitals together with the key statutes used are discussed. This paper also highlights the provisions and ramifications of the 11 April 2000 landmark agreement that Aetna made with Texas Attorney General John Cornyn to settle the 1998 lawsuit brought against the company. Lastly, the current ethical issues in the managed care industry are further discussed. The value of this paper can be adapted to the study of organizations' service fairness violations in other industries or in the educational, governmental, and not-for-profit sectors both nationally and internationally.